From oxypropylated olive stone towards novel polymeric materials - Matos, M.C. (2011)
The oxypropylation of OH-bearing substrates constitutes an original approach to the rational exploitation of the biomass. Total oxypropylation of a variety of natural polymers, including chitosan and chitin residues, different types of lignins, cork and more complex structures like sugar beet pulp, converts these solids, often otherwise intractable biomass residues, into liquid polyols thanks to the introduction of oligo(propylene oxide) grafts. The transformation of these polyols into rigid polyurethane (RPU) foams has been to date the main studied application. Following our previous work dealing with the optimization of the OS oxypropylation process, the purpose of this work is to explore the possibility of chemically modify the generated polyols through reactions with isocyanates and acid chlorides (or carboxylic acid esters) to produce polyurethanes and polyesters, respectively. Two different approaches have been used, namely (1) the use of monofunctional reagents in order to modulate the final polyol properties, namely lowering the hydroxyl functionality and (2) the use of difunctional reagents to produce more elaborate macromolecular materials, including networks.